Exploring the Role of Community-Based Partnership for Enhancing Academic Achievement : Empowering Students Through Quality Teaching - Wilfridus Vinsentius Sarah; Bambang Ismanto; Herry Sanoto (Jurnal Kependidikan: Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran dan Pembelajaran, 2023)
This research aims to investigates the impact of community-based partnerships on teacher teaching quality and student academic achievement. This study used a quantitative approach with structural equation analysis. The target population was 5 Catholic Junior High Schools (SMP) and Senior High Schools (SMA) in the city of Sibolga Gunungsitoli, Nias, North Sumatra, with details of 28 teachers for Saverius High School, 27 teachers for Fransikus High School, 27 Kesuma Indah High School teachers, 27 teachers for Bunga Middle School, Mawar 28 teachers, Kesuma Indah Middle School 21 teachers, and Francis Middle School 20 (teachers), bringing a total sample of 189. Confirmatory factor analysis (CFA) and hypothesis testing used the structural equation model through AMOS version 26.00. The results showed that Community-based partnerships in education could significantly positively impact teacher teaching quality and student academic achievement. Through collaboration between schools, communities, and teachers, this approach allowed for improvements in the quality of teaching that directly impact student academic achievement. These findings also support the theory of motivation, which asserts that community-based partnerships can increase student motivation through quality teaching and support from community members.